A microfluidic timer for timed valving and pumping in centrifugal microfluidics1. Issue 6 (21st March 2015) - Schwemmer, F.; Zehnle, S.; Mark, D.; von Stetten, F.; Zengerle, R.; Paust, N.
<x xml:space="preserve">Abstract</x> The microfluidic timer, a new unit operation for timing of valving and pumping in centrifugal microfluidics.